Customer engagement on live streaming: a socio-technical approach - Yudha Dwi Nugraha; Annisa Nadiyah Rahmani; Khumairah Khumairah; Hendy Mustiko Aji (Universitas Negeri Surabaya, Indonesia, 2024)
Technological advancements impact the e-commerce business landscape and give rise to live streaming shopping. This study, using a socio-technical approach, aims to investigate the relationship between interaction, emotional attachment, synchronicity, platform attachment, visit duration, and customer engagement. The data was collected using an online survey of 111 users. The Structural Equation Model was employed to evaluate five hypotheses. The results indicate that interaction has a positive and significant relationship with emotional attachment. However, this study found that there was no significant relationship between synchronicity and platform attachment. Furthermore, the study proved a positive and significant relationship between emotional attachment and visit duration. The study also found a positive and significant relationship between platform attachments and visit duration. Finally, visit duration has a positive and significant effect on customer engagement. This study adds to the existing literature on customer engagement and marketing by utilising a socio-technical approach to identify the factors that influence customer engagement on TikTok Shop. In the practical context, a live streaming platform can enhance customer engagement among Indonesian consumers by extending their visit duration on the TikTok Shop platform. They can also maximise emotional attachment by focusing on optimising the interaction between streamers and viewers. In terms of social benefits, consumers have a variety of live shopping platforms to choose from. TikTok Shop serves as a bridge to overcome the need for physical interaction between consumers, products, and sellers.